IMPLEMENTASI PROGRAM MUHADHOROH DALAM MENINGKATKAN KREATIVITAS BELAJAR DAN PRESTASI SANTRI DI PONDOK PESANTREN KOTA BATAM - Hamdani Afif; Muhammad Juni Beddu; Nur'aini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The muhadhoroh program is a learning activity in Islamic boarding schools aimed at improving communication skills, enhancing self-confidence, and developing students’ creativity. However, its implementation still faces challenges, including low participation and limited student readiness in delivering materials. This study aims to analyze the implementation of the muhadhoroh program in improving students’ learning creativity and academic achievement in Islamic boarding schools in Batam City, as well as to identify supporting and inhibiting factors. This research employed a descriptive qualitative approach involving 100 students through questionnaires and 20 students and 5 teachers through in-depth interviews. Data were collected through observation, interviews, documentation, and questionnaires, and analyzed using data reduction, data display, and conclusion drawing with triangulation. The findings indicate that the muhadhoroh program has been implemented effectively and positively impacts students’ creativity, critical thinking, communication skills, and self-confidence. It also contributes to improved academic achievement. Therefore, the program should be developed systematically and sustainably.